Comparison of three different acidic solutions in tendon decellularized extracellular matrix bio-ink fabrication for 3D cell printing. (1st September 2021) - Zhao, Fengyuan; Cheng, Jin; Zhang, Jiahao; Yu, Huilei; Dai, Wenli; Yan, Wenqiang; Sun, Muyang; Ding, Guocheng; Li, Qi; Meng, Qingyang; Liu, Qiang; Duan, Xiaoning; et al.
Abstract: Decellularized extracellular matrix (dECM) hydrogels are being increasingly investigated for use in bio-inks for three-dimensional cell printing given their good cytocompatibility and biomimetic properties. The osmotic pressure and stiffness of bio-ink are important factors affecting the biological functions of printed cells. However, little attention has been given to the osmotic pressure and stiffness of the dECM bio-inks. Here, we compared three types of commonly used acidic solutions in the bio-fabrication of a tendon derived dECM bio-ink for 3D cell printing (0.5 M acetic acid, 0.1 M hydrochloric acid and 0.02 M hydrochloric acid). We found that low pH value of 0.1 M hydrochloric acid could accelerate the digestion process for dECM powders. This could lead to a much softer dECM hydrogel with storage modulus less than 100 Pa. This soft dECM hydrogel facilitated the spreading and proliferation of stem cells encapsulated within it. It also showed better tendon-inducing ability compared with two others much stiffer dECM hydrogels. However, this over-digested dECM hydrogel was more unstable as it could shrink with the culture time going on. For 0.5 M acetic acid made dECM bio-ink, the hyperosmotic state of the bio-ink led to much lower cellular viability rates. Postprocess (Dilution or dialysis) to tailor the osmotic pressure of hydrogels could be a necessary step before mixed with cells. Thus, kindly choosing the type and concentration of acidic solution is necessary for dECM bio-ink preparation. And a balance should be made between the digestion period, strength of acidic solution, as well as the size and concentration of the dECM powders. Statement of significance: The dECM bio-ink has been widely used in 3D cell printing for tissue engineering and organ modelling. In this study, we found that different types of acid have different digestion and dissolution status for the dECM materials. A much softer tendon derived dECM hydrogel with lower stiffness could facilitate the cellular spreading, proliferation and tendon differentiation. We also demonstrated that the osmotic pressure should be taken care of in the preparation of dECM bio-ink with 0.5 M acetic acid. Thus, kindly choosing the type and concentration of acidic solution is necessary for dECM bio-ink preparation. Graphical Abstract: Image, graphical abstract